DIRECTIONS FOR THE IMPLEMENTATION OF GREEN ECONOMY PRINCIPLES IN THE SERVICE SECTOR - Suvonov, Ibrokhim Izbosarovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the theoretical foundations, practical mechanisms, existing challenges, as well as proposals and recommendations for implementing green economy principles in the services sector. The article aims to highlight the prospects for environmental transformation of the services sector in Uzbekistan.